The Role Of Digital Marketing In Improving Marketing Performance: A Systematic Literature Review - Denny Astanto; Rika Liftiana; Danang Apriliyanto (CV Pena Jaya Pers, 2025)
Purpose:Digital marketing has become a critical strategic tool for organizations seeking to improve marketing performance in an increasingly digital and competitive environment. This study aims to systematically review and synthesize the role of digital marketing in enhancing marketing performance, while identifying key dimensions, research trends, and gaps in the existing management and marketing literature. Design/methodology/approach: This study employs a systematic literature review by analyzing peer-reviewed journal articles indexed in reputable databases such as Scopus and Sinta. The review process follows the PRISMA guidelines, with clearly defined inclusion and exclusion criteria to ensure transparency, consistency, and methodological rigor. Findings:The results indicate that digital marketing has a significant positive impact on marketing performance through various mechanisms, including increased brand awareness, customer engagement, customer satisfaction, and sales performance. Social media marketing, content marketing, search engine optimization, and digital advertising emerge as the most frequently examined digital marketing practices. Research limitations/implications:This review is limited to selected databases and publication periods, which may restrict the comprehensiveness of the findings. Future research is encouraged to employ longitudinal designs and explore contextual factors, particularly in emerging economies. Practical implications:The findings provide practical insights for managers to design and implement effective digital marketing strategies aimed at improving overall marketing performance and sustaining competitive advantage. Originality/value:This study offers an integrative synthesis of digital marketing research and contributes to the literature by identifying dominant themes, methodological patterns, and future research directions. Paper type: Literature review